ANALISIS KESULITAN PENULISAN KATA BERIMBUHAN PADA MATA PELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Ratna Widyawati; Purnomo, Heru (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
The purpose of this study was to determine the obstacles experienced by fourth grade students of Lemahrubuh Elementary School in writing affixed words in the Indonesian Language subject. Writing skills are included in fairly complex language skills, because students must not only understand the meaning of basic words, but also be able to use affixes correctly according to grammatical rules. The approach used in this study is descriptive qualitative, with data collection methods through observation, interviews, and questionnaires. The research findings show that students still have difficulty in identifying and using prefixes, infixes, and suffixes correctly. This difficulty is caused by limited vocabulary, lack of variety in teaching methods, minimal use of interactive learning media, and lack of parental involvement in assisting children's learning process. In addition, online learning also affects students' less than optimal understanding. However, students' understanding tends to increase when teachers use interesting learning media and deliver material through real examples. Therefore, a more comprehensive teaching strategy is needed by optimizing creative learning media, increasing parental involvement, and implementing periodic evaluations so that students' ability to write affixed words can develop optimally.